Evaluation of the quality of boreholes water using indicators like Water Quality Index (WQI), and the Comprehensive Pollution Index (CPI) - Soughra Dah Soueilem; Abdoulaye Demba N’diaye; Ould El Moustapha Abdellahi; Bocar Kalidou M’Baye; Youssef Aoulad El Hadj Ali; Mohamed El Kory Cheikh Abeidou; Belkheir Hammouti; Rachid Sabbahi; Khalil Azzaoui; Shehdeh Jodeh; Mohamed Kankou (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
Mauritania is a country with a water deficit. The majority of these regions are supplied by groundwater through boreholes. Among these regions there is the Wilaya of Akjoujt. Water for domestic use from two boreholes in Benichab in the Wilaya of Inchiri was analyzed and assessed for quality in February, July and November 2023, using standard laboratory sampling and analysis methods. Parameters examined included temperature, pH, electrical conductivity (EC), Total dissolved solids (TDS), turbidity, chlorides (Cl-), nitrates (NO3-), sulfates (SO42-), calcium (Ca2+), magnesium (Mg2+), sodium (Na+), potassium (K+) and fluoride (F-). The results of the physico-chemical analysis demonstrated that the borehole water met World Health Organization (WHO) standards for human consumption. Water quality index (WQI) and Comprehensive Pollution Index (CPI) methods were used. The WQI confirmed that water from the Benichab boreholes, with a score below 50, was excellent for consumption. CPI values ranged from 0.22 to 0.27, suggesting slightly impaired borehole water at Benichab. However, without considering F- and pH, CPI ranged from 0.14 to 0.20, indicating satisfactory borehole water quality in the Benichab region. These results underline the importance of F- and pH in borehole water quality in Benichab. A statistical analysis of the correlation between F- and certain physical parameters using Pearson's correlation matrix revealed that F- concentrations could be influenced by pH in Benichab boreholes. The affirmative solution will be a continuous water quality monitoring program particularly F- and pH and a detailed hydrogeochemical investigation is suggested for sustainable utilization of water resources